2019
DOI: 10.1167/19.11.13
|View full text |Cite
|
Sign up to set email alerts
|

Predictive coding in a multisensory path integration task: An fMRI study

Abstract: This work is licensed under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License. Downloaded from jov.arvojournals.org on 09/03/2020 areas was enhanced in a modality-specific manner. We conclude that the effect of action on sensory processing is strictly dependent on the respective behavioral task and its relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 63 publications
(80 reference statements)
2
9
0
Order By: Relevance
“…In contrast, previous fMRI-studies focusing on the neural underpinnings of occluded moving objects often failed to observe evidence for the involvement of low-level visual areas and rather observed a recruitment of parietal regions especially intraparietal sulcus (IPS), (O'Reilly et al, 2008;Shuwairi et al, 2007); or reported decreased fMRI-signals in these regions instead (Olson et al, 2004). An alternative hypothesis, in accord with this reduction of fMRI-signal in lowlevel visual areas, would be that inference of predictable trajectories reduce neural activity, similar to signal decrease in other highly predictable environment in a variety of tasks (Alink et al, 2010;Krala et al, 2019;van Heusden et al, 2019). This hypothesis is in line with the hierarchical predictive coding model of Rao and Ballard (1999), which postulates that feedback and feedforward connections convey predictions to lower levels and error estimates to higher levels, respectively, and that deviations from a predicted outcome would lead to enhanced signalling in low-level areas.…”
mentioning
confidence: 99%
“…In contrast, previous fMRI-studies focusing on the neural underpinnings of occluded moving objects often failed to observe evidence for the involvement of low-level visual areas and rather observed a recruitment of parietal regions especially intraparietal sulcus (IPS), (O'Reilly et al, 2008;Shuwairi et al, 2007); or reported decreased fMRI-signals in these regions instead (Olson et al, 2004). An alternative hypothesis, in accord with this reduction of fMRI-signal in lowlevel visual areas, would be that inference of predictable trajectories reduce neural activity, similar to signal decrease in other highly predictable environment in a variety of tasks (Alink et al, 2010;Krala et al, 2019;van Heusden et al, 2019). This hypothesis is in line with the hierarchical predictive coding model of Rao and Ballard (1999), which postulates that feedback and feedforward connections convey predictions to lower levels and error estimates to higher levels, respectively, and that deviations from a predicted outcome would lead to enhanced signalling in low-level areas.…”
mentioning
confidence: 99%
“…Besides Rao and Ballard, others also attempted to mathematically explain how different systems works, by varying how the model is applied to the data and how the error is minimized (for review, see Spratling, 2017; Aitchison & Lengyel, 2017). Predictive Coding models have been used to test the mechanisms underlying temporal and spatial predictions in different domains, such as auditory (Baess et al, 2009; Heilbron & Chait, 2018, for review), motor (Shipp, Adams, & Friston, 2013), multisensory integration (Krala et al 2019) and the visual domain.…”
Section: Introductionmentioning
confidence: 99%
“…Coding models have been used to test the mechanisms underlying temporal and spatial predictions in different domains, such as auditory (Baess et al, 2009;Heilbron & Chait, 2018, for review), motor (Shipp, Adams, & Friston, 2013), multisensory integration (Krala et al 2019) and the visual domain.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, previous fMRI-studies focusing on the neural underpinnings of occluded moving objects often failed to observe evidence for the involvement of low-level visual areas and rather observed a recruitment of parietal regions especially intraparietal sulcus (IPS), (Shuwairi et al, 2007;O'Reilly, Mesulam, & Nobre, 2008); or reported decreased fMRI-signals in these regions instead (Olson et al, 2003). An alternative hypothesis, in accord with this reduction of fMRI-signal in low-level visual areas, would be that inference of predictable trajectories reduce neural activity, similar to signal decrease in other highly predictable environment in a variety of tasks (Alink et al, 2010, Krala, et al, 2019, van Heusden et al, 2019. This hypothesis is in line with Rao and Ballard's (1999) hierarchical predictive coding model, which postulates that feedback and feedforward connections convey predictions to lower levels and error estimates to higher levels, respectively, and that deviations from a predicted outcome would lead to enhanced signalling in low-level areas.…”
Section: Introductionmentioning
confidence: 99%